Preparatory Switches of Auditory Spatial and Non-Spatial Attention Among Simultaneous Voices - Aureliu Lavric; Elisa Schmied (Journal of Cognition)
Can one shift attention among voices at a cocktail party during a silent pause? Researchers have required participants to attend to one of two simultaneous voices – cued by its gender or location. Switching the target gender or location has resulted in a performance ‘switch cost’ – which was recently shown to reduce with preparation when a gender cue was presented in advance. The current study asks if preparation for a switch is also effective when a voice is selected by location. We displayed a word or image 50/800/1400 ms before the onset of two simultaneous dichotic (male and female) voices to indicate whether participants should classify as odd/even the number spoken by the voice on the left or on the right; in another condition, we used gender cues. Preparation reduced the switch cost in both spatial-and gender-cueing conditions. Performance was better when each voice was heard on the same side as on the preceding trial, suggesting ‘binding’ of non-spatial and spatial voice features – but this did not materially influence the reduction in switch cost with preparation, indicating that preparatory attentional shifts can be effective within a single (task-relevant) dimension. We also asked whether words or pictures are more effective for cueing a voice. Picture cues resulted in better performance than word cues, especially when the interval between the cue and the stimulus was short, suggesting that (presumably phonological) processes involved in the recognition of the word cue interfered with the (near) concurrent encoding of the target voice’s speech.